1999
DOI: 10.1016/s0009-9236(99)70133-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grapefruit juice on cisapride pharmacokinetics

Abstract: Grapefruit juice increases the oral bioavailability of cisapride, with large interindividual variation in the change in Cmax and AUC. Because cisapride has a wide therapeutic index, the interaction may not be of major clinical significance for efficacy, but further studies are necessary at steady state to rule out the possibility of side effects in susceptible individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 20 publications
5
37
2
Order By: Relevance
“…The mean C max increased 160%, and the AUC increased 190%. The effect of grapefruit juice on the bioavailability of praziquantel showed an interindividual variability similar to that found with other drugs (11,13).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The mean C max increased 160%, and the AUC increased 190%. The effect of grapefruit juice on the bioavailability of praziquantel showed an interindividual variability similar to that found with other drugs (11,13).…”
supporting
confidence: 76%
“…No statistically significant differences were found in the time to maximum concentration of drug in plasma or elimination half-life.Grapefruit juice increases the bioavailability of a variety of drugs (3,4,10,11,13,14,18), but it scarcely affects the elimination half-life (t 1/2 ). These findings suggest that grapefruit juice alters the first-pass metabolism mainly by suppression of the cytochrome P450 enzyme CYP3A4 in the small intestine (1,2,15).…”
mentioning
confidence: 99%
“…CYP3A4 is the primary mode of elimination of cisapride (Bohets et al, 2000). In two different studies, 250 ml of grapefruit juice ingested concomitantly with a 10 mg dose of cizapride caused a 50% increase in the bioavailability of cizapride (Gross et al, 1999;Offman et al, 2001). In another study, high doses of grapefruit juice were used and similar outcomes have been reported .…”
Section: Sildenafilmentioning
confidence: 70%
“…Cisapride pharmacokinetics have mainly been studied in adults [15,16,17,18]. Bioavailability is 40% to 50% when the drug is administered 15 min before meals, and maximal concentration is obtained in 1 h to 2 h [15].…”
Section: Introductionmentioning
confidence: 99%